Determination of cytotoxicity of traditional Chinese medicine herbs, Rhizoma coptidis, Radix scutellariae, and Cortex phellodendri, by three methods. Issue 2 (April 2016) - Boost, Maureen; Yau, Philip; Yap, Maurice; Cho, Pauline
Abstract: Background: Many herbs are used in traditional Chinese medicine TCM) for treatment of infections but their properties, in particular, their effects on normal cells have received little attention. This study investigated the cytotoxic properties of three TCM herbs with potential use in prevention and treatment of ocular infections, including Acanthamoeba keratitis . Method: The study investigated cytotoxic effects of the herbal extracts of Rhizoma coptidis, Radix scutellariae, and Cortex phellodendri on human corneal epithelial cells using trypan blue staining, MTT production, and flow cytometry. Differences between herbs were determined using repeated measures one-way analysis of variance, followed by paired t -tests where appropriate. Results: These three herbs appeared to lack cytotoxicity when tested with trypan blue and MTT, but flow cytometry revealed that R . coptidis led to cell membrane damage. Conclusion: Lack of cytotoxicity of R . scutellariae and C . phellodendri extracts suggest that these are potentially suitable for use in ocular preparations. Only flow cytometry was able to accurately predict cytotoxic effects of extracts of TCM herbs on HCEC, demonstrating the importance of using a sensitive method of detection of cytotoxicity.